2011
DOI: 10.1093/jmt/48.4.440
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Music Therapy Social Skills Training Program on Improving Social Competence in Children and Adolescents with Social Skills Deficits

Abstract: Three separate studies were conducted in school, residential and after-school care settings to test the effectiveness of a music therapy-based social skills intervention program on improving social competence in children and adolescents. A total of 45 children (n = 12; n = 13; n = 20) aged 6-17 years with social skills deficits participated in a group-based five session intervention program. The same curriculum, adapted to be age appropriate, was used at all 3 sites. Specific deficits within the social skills … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 0 publications
1
47
0
7
Order By: Relevance
“…This finding is consistent with research conducted by Keen (2011), James et al (2015), Geretsegger et al (2014), Gooding (2011), Mateos Moreno and Atencia Dona (2013), and Schwartzberg and Silverman (2013). They showed that activities related to MT facilitate social communication and dynamic, common, and active interaction in children with autism.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with research conducted by Keen (2011), James et al (2015), Geretsegger et al (2014), Gooding (2011), Mateos Moreno and Atencia Dona (2013), and Schwartzberg and Silverman (2013). They showed that activities related to MT facilitate social communication and dynamic, common, and active interaction in children with autism.…”
Section: Discussionsupporting
confidence: 90%
“…All disagreements were resolved through discussion between all authors. Papers were excluded because the participants were not children (Cardaciotto and Herbert 2004;Hare 1997;Kruzynski 1998;Perry 2008;Weiss and Lunsky 2010;Zelazo 1997), they were not intervention studies reporting on outcomes (Attwood 2004;Barsky 2001;Gratton 2010), the author did not explicitly describe the intervention as cognitive-behavioral (Lerner 2013;Snell 2012), the participants did not have a reported diagnosis of ASD (Fitzgerald and Werner 1996;Grosso 2012), or because they included participants with or without ASD and outcomes for participants with ASD were not reported separately (Epp 2008;Gooding 2010;Kellner and Tutin 1995;Lim et al 2007). The other excluded reports were either not written in English, did not report on intervention outcomes, or did not use a CBA.…”
Section: Methodsmentioning
confidence: 99%
“…Similar awareness is seen in music therapy: First, the growing interest within the discipline in how music is used in other contexts than music therapy (e.g., Aigen, 2012; Solli, 2008) might be understood as an articulation of this level of context awareness. Second, the musical-cultural context can be related to the goals and aims for music therapy, such as the development of musical skills (Rolvsjord, 2001), improvement of communication and social skills (Gooding, 2011; Grocke, 2009; Hannibal, 2003), or the promotion of enablement and cultural capital (Procter, 2001, 2004, 2011). Third, concerns for music therapy have been articulated in terms of access to music (Aigen, 2005a; Rolvsjord, 2010; Ruud, 1996; Stige & Aarø, 2012).…”
Section: Music Therapy In Contextmentioning
confidence: 99%